Surrender to the Highlander - Sands, Lynsay (Sands, Lynsay. Highland brides., 2018)
Edith Drummond owes her life to Niels Buchanan and his brothers. Waking after an illness to a castle overrun by rugged Highlanders is disconcerting, but so is learning that she<U+2019>s slowly being poisoned. Niels insists on staying by her side, and Edith soon discovers that even more dangerous is her wild attraction to the fierce warrior. Niels has never met a more courageous<U+2014>or enticing<U+2014>woman than Lady Edith. The idea of such a bonny lass being forced to enter a nunnery is more than any red-blooded Scotsman could bear. He<U+2019>ll gladly marry her himself. But while sweeping her off her feet is easy, it<U+2019>ll take all his skill to defeat her family<U+2019>s relentless enemies, and convince her to surrender to his sweet embrace. . . .